Garra robertsi, a new cyprinid (Cypriniformes: Cyprinidae) fish species from Borneo - Thoni, Ryan J.; Mayden, Richard L. (Zootaxa, 2015)
Garra robertsi is described from specimens collected from the Sungai Bongan and Tempassuk rivers in Sabah, Borneo. The species is differentiated from G. borneensis, its only congener on the island of Borneo, in having five (versus four) transverse scale rows above lateral line, the first branched dorsal-fin ray extending beyond the posterior-most extent of any other part of the dorsal fin when depressed (versus not extending posteriorly beyond last ray when depressed), breast with deeply embedded scales (versus exposed scales), fewer tubercles on snout, thin (versus thick) anteromedial fold on the lower lip, absence (versus presence) of a lateral stripe, absence (versus presence) of a stark, contrasting black stripe on lower caudal-fin rays, and other pigmentation characteristics.